Descripción del desarrollo embrionario de zigotos híbridos obtenidos por el cruce de machos de Cachama Blanca (Piaractus brachypomus) y hembras de Cachama Negra (Colossoma macropomum) (2004)
ABSTRACT: Three male Piaractus brachypomus and three female Colossoma macropomum were selected, all of them were in a range of 2.5 to 3 years of age. They were treated with CPE depending on their sexual maturation status. Fertilization was performed “on dry” and ascendant flow incubators were used. A 0.1% sample was taken every 10 to 15 minutes and it’s characteristics were described. The egg begins to hydrate it self, the corium separates from the vitelum. At 00:08 minutes the zygote period starts, the blastocyst forms itself and the perivitelin space appears. Then at 00:10 minutes starts the cleavage period and between 10 minutes and 1:45 hours post fertilization occurs the 2 to 64 cell development. The blastule and gastrule period are characterized by the formation of the epiloby and the ectodermal tube (head to tail differentiation). At 10:05 hours there occurs the engolfing of the vitelum and at 11:00 hours the segmentation period begins and faringulation ensues, which corresponds to the development of somites (spinal cord rudiments) and formation of the basic organs, the optical vesicle and the segments of the mesoderm. At 17:10 hours the vitelin sac and the somites are clearly defined and at 19:00 hours there occurs the hatching of larva.